Bioassay-directed fractionation and salmonella mutagenicity of automobile and forklift diesel exhaust particles. - DeMarini, David M (2004)
Many pulmonary toxicity studies of diesel exhaust particles (DEPs) have used an automobile-generated sample (A-DEPs) whose mutagenicity has not been reported. In contrast, many mutagenicity studies of DEPs have used a forklift-generated sample (SRM 2975) that has been evaluated in only a few pulmonary toxicity studies. Therefore, we evaluated the mutagenicity of both DEPs in Salmonella coupled to a bioassay-directed fractionation. The percentage of extractable organic material (EOM) was 26.3% for A-DEPs and 2% for SRM 2975. Most of the A-EOM (~55%) eluted in the hexane fraction, reflecting the presence of alkanes and alkenes, typical of uncombusted fuel. In contrast, most of the SRM 2975 EOM (~58%) eluted in the polar methanol fraction, indicative of oxygenated and/or nitrated organics derived from combustion. Most of the direct-acting, base-substitution activity of the A-EOM eluted in the hexane/dichloromethane (DCM) fraction, but this activity eluted in the polar methanol fraction for the SRM 2975 EOM. The direct-acting frameshift mutagenicity eluted across fractions of A-EOM, whereas > 80% eluted only in the DCM fraction of SRM 2975 EOM. The A-DEPs were more mutagenic than SRM 2975 per mass of particle, having 227 times more polycyclic aromatic hydrocarbon-type and 8-45 more nitroarene-type mutagenic activity. These differences were associated with the different conditions under which the two DEP samples were generated and collected. A comprehensive understanding of the mechanisms responsible for the health effects of DEPs requires the evaluation of DEP standards for a variety of end points, and our results highlight the need for multidisciplinary studies on a variety of representative samples of DEPs.